Effectiveness of structured patient education on the knowledge level of adolescents and adults with congenital heart disease. (1st February 2014) - Goossens, Eva; Van Deyk, Kristien; Zupancic, Nele; Budts, Werner; Moons, Philip
Abstract: Background: Patients with congenital heart disease (CHD) have poor understanding of their heart condition, treatment and prevention of complications. To improve their level of health-related knowledge, a structured education program was implemented in the adult congenital heart disease program. This study aimed (a) to evaluate the level of knowledge of patients who received structured CHD education as compared to patients who did not receive this education; (b) to explore if the provision of structured education is an independent determinant of knowledge; and (c) to evaluate whether patients who received structured education reached the educational target (>80% correct answers). Methods and results: A total of 317 patients were included: 226 in the education group, and 91 in the comparison group. Knowledge was assessed using the 'Leuven Knowledge Questionnaire for Congenital Heart Disease'. The mean total knowledge score in the education group (57%) was significantly higher as compared to the comparison group (43%) ( p <0.001). However, only 24 patients (11%) in the education group reached the educational target of the program. After adjusting for patient's age, educational level and disease complexity, hierarchical multivariable linear regression analysis showed that the provision of structured CHD education was an independent determinant of higher levels of knowledge. Conclusion: A structured education program was associated with a higher level of knowledge. However, the educational target for sufficient knowledge was reached in a very limited number of patients. Hence, continuous efforts in educating patients and developing alternative education methods are needed.